Genetic analysis of Chios sheep: Identification of genetic variants and investigation of their association with milk traits. - Hadjipavlou, G.; Orford, Michael R.; Tzamaloukas, Ouranios; Chatziplis, Dimitrios G.; Koumas, Alkis; Mavrogenis, Andreas; Miltiadou, Despoina; Papachristoforou, Christakis (My University, 2012)
Dissecting the genetic basis of milk production traits would be of great benefit to the small ruminant dairy industry. The objective of this work was to identify genetic variants at loci that have been mainly mapped in dairy cattle, and investigate their effects on milk traits of Cyprus Chios sheep. For this purpose, 320 Chios ewes from a nucleus flock in Cyprus were genotyped for polymorphisms at the β-lactoglobulin (β-LG), prolactin (PRL), Growth Hormone Receptor (GHR), DGAT1, and Acetyl-Coenzyme A acyltransferase-2 (ACAA2) loci. The GHR F279Y and DGAT1 K232A variants were absent from Chios sheep. The common β-LG variants, A and B, and PRL variants were detected at intermediate frequencies but exhibited no association with milk traits. The entire coding region of ACAA2 was sequenced and a novel SNP (HM537015:g.2982T > C) was identified in the 3’ UTR, with both alleles segregating at similar frequencies. All other exons were monomorphic. Mixed model association analysis, using SNP data from 318 animals from 104 paternal half-sib families and first lactation phenotype and pedigree information on 2405 ewes revealed that this SNP was significantly associated with milk yield. The T allele was associated with increased milk yield, and exhibited partial dominant action. Animals with the g.2982TT or g.2982CT genotype had significantly higher milk yield than those with the g.2982CC genotype, with the g.2982T allele having an additive effect of 13.4(±4.7) kg and a dominance effect of 7.9(±6.1) kg. Based on estimated allelic effects and sample allele frequencies, the g.2982T>C SNP explained 10% of the additive genetic variance for milk yield. To the best of our knowledge, this is the first study reporting a significant association of an ACAA2 polymorphism with milk yield in ruminants. Whether this (or a closely linked) SNP is a quantitative trait nucleotide for milk yield remains to be determined.
Keywords: Milk Production; Dairy Industry; Cyprus Sheep; Milk Traits; Chios Sheep